The Impact of Oil Prices on Inflation in Jordan: The Philips Curve Model - Khalid Ali Dyab Almajali (Migration Letters, 2023)
This study uses the crude oil price worldwide as a variable in the Phillips function to analyze the effects of fluctuating global oil prices on the Jordanian economy. To accomplish this, the (short/long run) correlations between inflation, oil prices, unemployment, and interest rates were examined using the Auto Regressive for the Distributed Lag model. From the Q1 of 2004 through that of 2020, quarterly statistics are used in this analysis. According to a marginal coefficient, the rising oil prices variable has a long-term favorable beneficial effect on consumer prices (The Jordanian inflation rate will climb by 0.28% for every percent increase in oil prices.).